P1.22 Vitamin d and the vaginal microbiome: results from a blinded, randomised controlled trial. (8th July 2017) - Jb, Holm; He, X; Rm, Brotman; An, Turner
Abstract : Introduction: A blinded, randomised controlled trial (RCT) previously demonstrated no effect of vitamin D supplementation on recurrence of bacterial vaginosis (BV) diagnosed by Nugent score. Here, we examine archived samples to determine whether vitamin D supplementation affected trial participants' vaginal microbial composition. Methods: Women with symptomatic BV via Amsel criteria were recruited and treated with 500 mg of oral metronidazole at baseline. Participants were randomised to vitamin D supplementation (9 doses of 50, 000 IU cholecalciferol over 24 weeks) or matching placebo. Vaginal bacterial composition was characterised for 15 women in each treatment arm, using samples collected at baseline, 4 and 24 weeks. We sequenced the V1-V3 region of the 16S rRNA gene and taxonomy was assigned by PECAN. Microbiota were clustered into 5 community state types (CSTs) using Bray-Curtis distances and hierarchical clustering with Ward linkage. We assessed serum vitamin D levels using the Liaison 25 OH vitamin D total assay. Results: We observed no significant effect of vitamin D treatment on Lactobacillus dominance over 24 weeks (p>0.5). Additionally, serum vitamin D levels were not associated with CST (p=0.22). Following metronidazole treatment, the Lactobacillus iners -dominated CST (III) was more common at week 4 compared to enrollment in both the placebo and vitamin D groups. Specifically, the relative abundance of L. iners was significantly higher in the placebo arm at weeks 4 (p<0.001) and 24 (p=0.04) compared to the vitamin D arm. Conclusion: In agreement with the RCT, we observed no association between vitamin D supplementation and the vaginal microbiota. While many women in both RCT groups tended toward L. iners -dominated microbiotas following metronidazole treatment at week 4, L. iners was significantly more abundant in the placebo group. Future research may examine if vitamin D plays a role in stimulating non-lactobacilli growth and how supplements, in addition to antibiotics, affect the emergence of robust lactic acid producing lactobacilli.